Awareness of pediatric eye examination among parents in Selangor/ Wan Elhami Wan Omar and Nurul Afida Abdul Razak - Wan Omar, Wan Elhami; Abdul Razak, Nurul Afida (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The objective of this study was to determine the awareness level of pediatric eye examination among parents in Selangor. The study also aimed to determine the association of parents' educational and socio-economic background towards the awareness of pediatric eye examination. The study was a cross-sectional descriptive study. The survey was conducted using a collective administration questionnaire. Questionnaires were distributed to the parents with children of the age of 2 to 12 years old. The questionnaire consisted of information on demographics (gender, age) and parents' educational and socio-economic background. Out of 192 total number of respondents, 123 (64.15%) respondents were aware of the importance of pediatric eye examination while the other 69 (35.9%) respondents were not aware of it. Despite the high level of awareness towards pediatric eye examination among the respondents, there were 39 (20.3%) of them did not know that routine eye examination is necessary for their children's eye health and another 6 (3.1%) were not sure about it. There was no significant association between education level (r=0.199, p=0.06) and socio-economic background (r=0.01, p=0.99) and awareness level of pediatric eye examination among parents. There was still lack of practice regarding parents seeking good eye care health for their children. Therefore, health care practitioners, especially optometrist, need to increase pediatric eye health education through many sources. This will reinforce good pediatric eye care practice and allow the planning of preventive measure and early intervention that can help in avoiding visual disability and blindness in children.